25 'In a mist?' – What is 'brain fog'?. Issue 12 (14th November 2022) - Smyth, Heather; Hoeritzauer, Ingrid; Couturier, Anna; Stone, Jon; Carson, Alan; McWhirter, Laura
Abstract : Objectives: The term 'brain fog' is increasingly used in social and other media. But what is brain fog? What sort of experiences do people talk about when they talk about brain fog? And, in turn, what might this tell us about potential underlying pathophysiological mechanisms? In this study we examined first-person descriptions of brain fog in order to better understand a) the phenomenology of brain fog, and b) the causal attributions of those describing brain fog. We use this information to consider implications for clinical research. Methods: Data were scraped from the social media platform Reddit using Python. Posts containing 'brain fog' were identified between 27thOctober 2021 and 3rd November 2021. Those not describing or discussing brain fog as a symptom or experience were excluded. Potentially identifying information was removed prior to analysis. We undertook thematic analysis of containing subreddits (topic-specific discussion forums), causal attributions, and discrete brain fog experiences. Results: 1663 posts including the term 'brain fog' were identified, of which 717 met inclusion criteria. 44% (315/717) posts originated from subreddits concerned with illness and disease: including COVID-19 (87 posts), autoimmune, functional, neurodevelopmental, major psychiatric, and endocrine disorders. Brain fog was also discussed in subreddits about prescribed and non-prescribed drug use, and subreddits concerned with intentional restriction of masturbation ('nofap'). 141 first person descriptions of brain fog described overlapping concepts including: forgetfulness (51), difficulty concentrating (43), dissociative phenomena (34), perceived cognitive 'slowness' and excessive effort (26), communication difficulties (22), a feeling of 'fuzziness' or pressure in the head (10), and fatigue (9). 570 posts described a perceived cause of brain fog, of which half attributed brain fog to illness or disease (282/570) (the most common single attribution being 'long COVID' in 59/570 (10%)), followed by psychiatric conditions in 38/570 (7%). The second most common single attribution of brain fog, in 24/570 (24%), was restriction or excessive masturbation. Conclusions: Brain fog is discussed on the Reddit social media platform in association with a wide range of illnesses, diseases, drugs, and activities. The term is used to describe heterogeneous experiences, which do not map in a straightforward way to the domains enquired about during a 'cognitive' clinical examination, but include experiences of dissociation, fatigue, and excessive cognitive effort. Encouraging detailed description of subjective experiences – moving away from a psychometric testing approach and towards a phenomenological approach – might open new routes into understanding cognitive difficulties in health and disease.